Immune competence of cancer-reactive T cells generated de novo in adult tumor-bearing mice - May, Kenneth F. (American Society of Hematology, 2007)
The impact of timing of antigen introduction into fetus and neonates leads to the suggestion that pre-existing antigens are tolerogenic to immunocompetent cells generated thereafter. This hypothesis predicts that in patients with cancer who are undergoing bone marrow transplantation, newly produced T cells with specificity for pre-existing tumor cells will be inactivated by the tumor antigens in the host. Because the effect of tumor cells on developing cancer-reactive T cells has not been investigated, we set out to systematically analyze the impact of tumor cells in the periphery on the development of tumor-reactive T cells in the thymus and their immunocompetence in the periphery. Our data demonstrate that in the host in which a tumor is established in the periphery, the cancer-reactive T cells develop normally, remain fully immunocompetent, become activated in the periphery, and cause regression of large established tumors. The immunocompetence of T cells generated in an antigen-bearing host is also confirmed in a skin graft transplantation model.